EFL Students’ Perception in Indonesia and Taiwan on Using Artificial Intelligence to Enhance Writing Skills - Rafida, Tien; Suwandi, Suwandi; Ananda, Rusydi (Jurnal Ilmiah Peuradeun, 2024)
Technological advancements in education have introduced Artificial Intelligence (AI) as a transformative tool to enhance academic writing skills in English as a Foreign Language (EFL). This study explored EFL students’ perceptions in Indonesia and Taiwan regarding the role of AI in improving their writing abilities. Using qualitative research methods, data were collected through semi-structured interviews with 20 second-year students specializing in English at an Islamic State University in Indonesia and a National University in Taiwan, who actively use AI tools in their writing processes. Analysis based on Creswell’s thematic framework revealed positive perceptions of AI, with benefits such as improved grammar, sentence structure, paraphrasing skills, vocabulary enrichment, and efficiency in topic generation. However, concerns also emerged about excessive reliance on AI, reduced creativity, and issues of plagiarism and authenticity. These findings highlighted the dual-edged nature of AI in academic writing, emphasizing the need for careful integration and risk mitigation to fully leverage AI’s educational benefits. This research enriched the discourse on technological advancements in EFL education and provides insights for curriculum developers, educators, and policymakers to optimize AI use in academic settings. The practical implications of these findings included strategies to enhance the effectiveness of AI in education and foster innovation in EFL teaching.